Efficacy of water recycling technologies for treatment of coronavirus - Ow, Jie Liang (Nanyang Technological University, 2021)
Due to the threat of the ongoing SARS-CoV-2 pandemic to water security, the removal efficacy of surrogate coronavirus HCoV-OC43 (OC43) by 2 water recycling technologies, coagulation, and ultrafiltration (UF) were tested. These processes were selected as they are essential treatment processes for microbiological parameters. Wastewater samples were spiked with OC43 virus, which were passed through coagulation and UF tests to determine the log10 removal of the virus using real-time polymerase chain reaction (PCR) and compared with existing potable water reuse guidelines. Both treatment processes displayed a mean log removal value (LRV) of 0.94 and 1.57 logs respectively. When the coagulation process was combined with the use of coagulant aids, the mean LRV was 1.53 logs. Results from this final year project contributes to the ongoing efforts on how coronaviruses are removed in water and further studies on the use of ceramic membranes in UF.